2017
DOI: 10.1126/sciadv.1600957
|View full text |Cite
|
Sign up to set email alerts
|

A murine preclinical syngeneic transplantation model for breast cancer precision medicine

Abstract: This work presents a new preclinical platform for implementation of selected targeted therapeutics for breast cancer patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…3D ). Finally, we immunostained breast cancer tissue sections from a murine-derived syngeneic transplant model 14 for the CTL marker CD8 and found the immunostaining data was in good agreement with our RNAseq CTL score (Supplementary Fig. 3E ).…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…3D ). Finally, we immunostained breast cancer tissue sections from a murine-derived syngeneic transplant model 14 for the CTL marker CD8 and found the immunostaining data was in good agreement with our RNAseq CTL score (Supplementary Fig. 3E ).…”
Section: Resultssupporting
confidence: 66%
“…Finally, to verify this phenotype we utilized a preclinical murine syngeneic transplantation breast cancer model (Fig. 7a ) 14 . Within this model we found that phosphorylated ATM as quantified by RPPA showed significant positive correlation with CTL levels as determined by immunostaining for the marker CD8 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To address the lack of heterogeneity and pro duce a more humanlike model, biomedical scientist Lorenzo Federico and his colleagues, working in the laboratory of systems biologist Gordon Mills at the University of Texas MD Anderson Cancer Center in Houston, engi neered a collection of transplantable grafts from primary breast tumors in transgenic mice 3 . The procedure yielded 12 new graft lines of mice -mouse models that can reliably pro duce specific types of cancer with a wide array of genetic changes.…”
Section: Modified Mouse Genomesmentioning
confidence: 99%